2014
DOI: 10.1016/s1995-7645(13)60185-6
|View full text |Cite
|
Sign up to set email alerts
|

Emblica officinalis improves glycemic status and oxidative stress in STZ induced type 2 diabetic model rats

Abstract: The aqueous extract of E. officinalis has a promising antidiabetic and antioxidant properties and may be considered for further clinical studies in drug development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 17 publications
1
18
0
Order By: Relevance
“…The EO fruit extract reduces blood sugar levels. 41 , 42 Thus, caution should be taken when using hypoglycemic medications, and patients taking insulin or drugs for diabetes need to be monitored closely. In addition, EO decreases serum lipid levels; hence, cholesterol- or triglyceride-lowering medications should be taken with caution.…”
Section: Discussionmentioning
confidence: 99%
“…The EO fruit extract reduces blood sugar levels. 41 , 42 Thus, caution should be taken when using hypoglycemic medications, and patients taking insulin or drugs for diabetes need to be monitored closely. In addition, EO decreases serum lipid levels; hence, cholesterol- or triglyceride-lowering medications should be taken with caution.…”
Section: Discussionmentioning
confidence: 99%
“…Various parts of medicinal plants like leaves, roots, bark and fruit are used by Ayurvedic practitioners for different therapeutic effects as they are safe, economical, least adverse effects [9]. Literature reports that water-soluble [10] extract of Emblica officinalis has potent antioxidant activity and hypoglycemic activity [11]. Emblica officinalis Gaertn.…”
Section: Methodsmentioning
confidence: 99%
“…is also known as "Amla" traditionally, belonging to the family Euphorbiaceae [12]. It is one of the most important plants of Ayurveda and traditional Indian medicine [11]. Other reports indicate that marmelosin present in Aegle marmelos has antidiabetic activity [13][14][15][16].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Phyllanthus emblica L. fruit is mainly grown in tropical and subtropical regions, and enriches in a variety of biologically active compounds such as flavonoids, polyphenols and vitamin C. Previous studies have shown that the extract of P. emblica fruit can improve blood pressure, fatty liver, nonalcoholic steatohepatitis, diabetes, inflammation, antioxidant, and cancer (Fugh-Berman, 2000;Nain et al, 2012;Muthuraman et al, 2011;Ansari et al, 2014;Zhao et al, 2015;Tung et al, 2018). However, the effect of P. emblica fruit on methylglyoxal-induced insulin resistance remains unclear.…”
Section: Introductionmentioning
confidence: 99%